2000
DOI: 10.1046/j.1523-1747.2000.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-A-Induced Transactivation of the Vascular Endothelial Growth Factor Gene in HaCaT Keratinocytes is Conveyed by Activator Protein-2 Transcription Factor

Abstract: Ultraviolet-A radiation represents a significant proportion of the ultraviolet solar spectrum that was recently shown to affect gene expression of epidermal keratinocytes by molecular mechanisms distinct from ultraviolet-B radiation. As ultraviolet-A either alone or in combination with ultraviolet-B may contribute to photocarcinogenesis, we aimed to explore the biologic effects of ultraviolet-A radiation on vascular endothelial growth factor gene expression by the immortalized keratinocyte cell line HaCaT. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
27
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 34 publications
3
27
1
1
Order By: Relevance
“…Furthermore, immunohistochemical analyses of advanced primary and metastatic melanoma clinical specimens demonstrated that the loss of AP-2 expression correlated with low p21/WAF1, E-cadherin, and c-KIT expression and poor prognosis (7,8). Functional AP-2-binding elements have been identified in other genes involved in the progression of human melanoma, including p21/WAF1 (9), intercellular adhesion molecule (10), c-erbB-2/HER-2/neu (11)(12)(13), plasminogen activator inhibitor type I (14), insulin-like growth factor-binding protein-5 (15), transforming growth factor-␣ (16), vascular endothelial growth factor (17,18), E-cadherin (19), and hepatocyte growth factor (20).…”
mentioning
confidence: 99%
“…Furthermore, immunohistochemical analyses of advanced primary and metastatic melanoma clinical specimens demonstrated that the loss of AP-2 expression correlated with low p21/WAF1, E-cadherin, and c-KIT expression and poor prognosis (7,8). Functional AP-2-binding elements have been identified in other genes involved in the progression of human melanoma, including p21/WAF1 (9), intercellular adhesion molecule (10), c-erbB-2/HER-2/neu (11)(12)(13), plasminogen activator inhibitor type I (14), insulin-like growth factor-binding protein-5 (15), transforming growth factor-␣ (16), vascular endothelial growth factor (17,18), E-cadherin (19), and hepatocyte growth factor (20).…”
mentioning
confidence: 99%
“…For example, phorbol esters and signals that enhance cAMP levels induce AP-2 activity independently of protein synthesis, whereas retinoic acid treatment of teratocarcinoma cell lines results in a transient induction of AP-2 mRNA levels on the transcription level (Imagawa et al, 1987;Luscher et al, 1989;Buettner et al, 1993). Other signals demonstrated to stimulate AP-2 expression and activate transcription of target genes include ultraviolet-A radiation and singlet oxygen (Grether-Beck et al, 1996;Huang and Domann, 1998;Gille et al, 2000).…”
mentioning
confidence: 99%
“…In addition, inactivation of AP-2 in primary cutaneous melanoma cells (AP-2 positive) by means of a dominant-negative AP-2 gene (AP-2B) led to deregulation of the metalloproteinase MMP-2 gene and increased the cells tumor and metastatic potential in nude mice (Gershenwald et al, 2001). Furthermore, functional AP-2-binding elements have been identified in other genes involved in the progression of human melanoma such as p21/WAF1 (Zeng et al, 1997), intercellular adhesion molecule (I-CAM) (Grether-Beck et al, 1996), c-erbB-2/HER-2/neu (Hollywood and Hurst, 1993;Bosher et al, 1995;Turner et al, 1998), plasminogen activator inhibitor type I (PAI-1) (Descheemaeker et al, 1992), insulin-like growth factor binding protein-5 (Duan and Clemmons, 1995), transforming growth factor-alpha (TGF-a) (Wang et al, 1997), vascular endothelial growth factor/vascular permeability factor (VEGF/VPF) (Gille et al, 1997(Gille et al, , 2000, E-cadherin (Batsche et al, 1998), hepatocyte growth factor (HGF) , and c-Myc (Gaubatz et al, 1995). Loss of AP-2 was also observed in clinical specimens of advanced primary and metastatic melanoma, which was associated with malignant transformation and elevated risk of tumor progression (Karjalainen et al, 1998;Baldi et al, 2001), thus supporting the hypothesis that loss of AP-2 is a crucial event in the progression and metastasis of melanoma.…”
mentioning
confidence: 99%
“…Skin hypoxia also leads to up-regulation of VEGF expression in epidermal keratinocytes, dermal fibroblasts, and dermal endothelial cells (15). The cloned 3.4-kb fragment of the VEGF promoter (2) contains consensus sequences that bind a variety of transcription factors, including hypoxia-induced factor (16), AP-1 (17), SP-1 (18), and AP-2 (19). Blocking of NFκB inhibits VEGF expression (20)(21)(22) and therefore it is likely that NFκB transcriptionally regulates VEGF mRNA.…”
mentioning
confidence: 99%
“…In addition to these factors, ultraviolet-A (UVA) has been reported to up-regulate VEGF in immortalized keratinocytes (HaCaT cells), presumably through activation of AP-2 (19) and maybe other as yet unidentified mechanisms. ultraviolet-B (UVB) radiation also induces VEGF expression in normal human keratinocytes, HaCaT cells, and A431 squamous carcinoma cells (23,24) and is thought to act indirectly by inducing the synthesis and release of IL-1, TNF-α, and other cytokines (23)(24)(25).…”
mentioning
confidence: 99%